Optimizing genomic DNA extraction from long-term preserved formalin-fixed and paraffin-embedded lung cancer and lymph node tissues - C.S. Faria; C.M. Baldavira; F.R.R. Mangone; M.E.M. Agati; L.D. Kulikowski; M.A. Nagai; E.C.T. do Nascimento; E.S. de Mello; V.L. Capelozzi; L. Antonangelo (Brazilian Journal of Medical and Biological Research)
Personalized therapy in lung cancer (LC) has revolutionized routine histopathology and cytopathology, emphasizing the importance of obtaining adequate material for molecular studies to support oncological decisions. Adaptations of cytologic sample preparations offer benefits for molecular testing, yet their potential remains underutilized. A significant number of LC cases is identified through specimens of aspiration or exfoliative cytology. Improving screening approaches and optimizing tissue utilization for biomarker research are crucial for effective LC management. The utilization of formalin-fixed, paraffin-embedded (FFPE) tumor tissues has become standard practice in clinical and epidemiological genetic research. However, current techniques require not only a standardized sample fixation and storage but also sufficient genetic material to yield reliable results. In this study, we utilized the Qiagen GeneRead® DNA FFPE kit with an adapted protocol for two extraction methods: one involved cutting FFPE blocks and the other involved scraping tissue from slides used for histochemical and cytological analysis. Our findings emphasized the importance of increasing the number of FFPE sections, heat deparaffinization, and adjusting proteinase K digestion time to enhance genomic DNA (gDNA) yields. Notably, scraping tissue from slides yielded superior results compared to the standard FFPE protocol. A median of 2.82 and 4.34 DNA yields for tumor and lymph node, respectively, were obtained. Our results demonstrated the feasibility of this adapted protocol for gDNA extraction in clinical and epidemiological studies. We recommend scraping tissue from slides as a reliable source of gDNA and suggest fine-tuning proteinase K digestion time and heat exposure based on the input tissue volume.